PENGARUH KETERAMPILAN BERKOMUNIKASI SAINS TERHADAP PENGUASAAN KONSEP FISIKA SISWA - Pujiati Pujiati; I Dewa Putu Nyeneng; Feriansyah Sesunan (Jurnal Pembelajaran Fisika, 2013)
Communication skills influence of science on students' mastery of physics concepts in a static fluid material, especially static fluid, which requires the student's ability to perform trial and analyze experimental results in order to assist them in understanding the concept. The teachers, who are involved in the process of teaching materials, need to choose the right way to do lab work. Through this technique, students create the concepts and solve problems easily. The purpose of this experiment was to determine the increase in student’s mastery of physics concepts using science communication skills and influence skills to communicate science to students' mastery of physics concepts in a static fluid material. Results of this study indicate that there is an increasing mastery of concepts by 0.55 and there is a linear effect of body skills to communicate science to the physics students' mastery of concepts by 14%. The degree of relationship between science communication skills and mastery of concepts have a influence strong relationship. Also contributed positively influence occurred.Kata kunci: keterampilan berkomunikasi sains, penguasaan konsep, peningkaatan penguasaan konsep